Rancang Bangun Alat Penentuan Kematangan Buah Melon Dengan Sensor Max9814 dan Soil Moisture Menggunakan Fuzzy (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2020)
In the agricultural sector, farmers and buyers have difficulty identifying agricultural products that are ready to harvest and are ripe, therefore we need a tool that can help to measure the level of maturity in agricultural products, especially in fruits and in this study focused on fruit melons, and to identify the ripeness of the melons, they are identified based on the moisture content and sound of the melons when they are tapped, which uses the Arduino Mega 2560 as the controller and the soil moisture sensor as a sensor to measure air content and the MAX9814 sound sensor to measure the sound or sound produced by the melon. Tapped, in this study a test scheme was carried out by comparing the results of the data between 10 raw melons, 10 medium melons, and 10 ripe melons as reference data for values ​​to be used and then processed using the fuzzy method, with the first stage the melons were taken using a sensor. soft soil n then the sound data is taken after tapping using a pendulum and then the data is entered into the fuzzy method rules that have been determined and data can be taken that the ripe melon has a moisture content of more than 70% while medium melon is 60-70% and raw melon from 60% for the sound produced, the greater the amplitude of the melon sound, the greater the maturity level because the cavity in the melon is getting bigger, there were several errors during the experiment because the sound that disturbed the sensor signal was awakened by an increased rate of 93%.